Assessing surface seals of soils on slopes - Liu, Chenying (2017)
Past research has observed that infiltration on surface soil which is subjected to frequent rainfall does not start as soon as precipitation begins. This phenomenon is attributed to the formation of a thin dense layer called surface seal on the surface soil. The surface seal is created by interaction forces between water and soil particles such as compaction, attachment, dispersion and so on. Surface seal formation plays a significant role in the process of slope erosion. The presence of the surface seal leads to the decrease of infiltration and increase in surface runoff which greatly enhances the possibility of erosion occurring. The objective of this project is to ascertain the existence of surface seal on the surface of a residual soil slope by analyzing and summarizing data and parameters obtained from field tests and laboratory experiments which were conducted on the surface soils. Infiltrometer tests were carried out at twelve locations at the crest, the face and the toe of a residual soil slope. Quick draw tensiometer test was also performed at the same location to provide corroboration of infiltration rate. Flexible wall falling-head permeability test was used to determine the saturated permeability of the soil in the laboratory. Pressure plate test was used to determine the soil-water characteristic curve (SWCC) of the soil samples. Specific gravity and hydrometer test was used to obtain α and n parameters in the van Genuchten SWCC equation. Permeability differences were used to determine the presence of a surface seal. The conclusion is drawn that surface seal appears to exist only at the crest of the slope. Van Genuchten parameters obtained from soil textures are consistent with those estimated from SWCC. Recommendations for future research are given at the end of the report.